Peningkatan Kemampuan dalam Membaca pada Permulaan melalui Media Kartu Kata Bergambar pada Anak Usia Dini 5-6 Tahun - Rosmidar Rosmidar; Robiatul Adawiyah; Junita Irawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Beginning readingability in childrenage5-6years is a basic skill that is very important in supporting their academic development. One effective method for improving this ability is through interesting and interactive media, such as picture word cards. This media is designed to introduce children to basic vocabulary with the help of appropriate pictures, and remember these words. Using picture word cards can strengthen children's reading skills, because they combine attractive visual elements with direct reading practice. Through fun games and activities, children can gradually learn to recognize words, improve their reading fluency and enrich their vocabulary. This approach also provides a pleasant experience, makes the process of learning to read more interesting and reduces the anxiety that may arise in children when learning to read. In this way, picture word cards become an effective medium in supporting the development of early reading skills in young children.